Translocation 21q22q in an infertile human male. Issue 5 (October 1982) - Chandley, A C; Hargreave, T B; Fletcher, J M
Abstract : Details are given of a balanced 21q22q Robertsonian translocation ascertained through infertility in a phenotypically normal male. Chromosome analyses on the proband and his parents showed that the translocation arose as a new mutation. The patient was oligospermic and had a high frequency of morphological abnormalities in his spermatozoa. Meiotic investigations showed a chain trivalent in all primary spermatocytes examined at diakinesis/metaphase I. The testicular histology was normal.